The differences between Western and Japanese academic culture: Their impact on the design and implementation of an EAP course at a Japanese university - Brooks, Steven (2016)
English for Academic Purposes (EAP) is a field that is gaining increasing prominence in Japan. As Japanese universities are charged with becoming more international in order to improve their performance in international university rankings, so the need to equip Japanese students to participate in English-medium courses of study abroad has grown. However, as well as the well-documented lack of confidence and ability in general English skills amongst young Japanese people, there is another factor which may hinder the teaching of EAP to Japanese university students, the vastly different culture that prevails in Japanese higher education institutions as opposed to those of the universities in English-speaking countries in the West. Therefore, this study was designed to assess the exact nature of these cultural differences in order to more fully understand what influence they have on the teaching of EAP in a Japanese university context. By conducting semi-structured interviews with EAP instructors, and questionnaires with EAP students, at a private university in Tokyo, this study is able to identify four general factors that illustrate the differences between Western and Japanese academic culture, and also to point to areas in which these differences may cause problems in the EAP classroom.